PENGARUH KOMPOSISI MEDIA TANAM (TOP SOIL ULTISOL, PASIR DAN PUPUK KANDANG KAMBING) TERHADAP PERTUMBUHAN BIBIT PORANG (AMORPHOPHALUS MUELLERI) - Matanari, Jawaller; Silitonga, Manaor; Hutauruk, Sixtus; Padang, Pasda Hotmarukur (AGROSUSTAIN, 2023)
This study aims to determine the effect of planting media (Top soil Ultisol, Sand and Goat Manure) on the growth of Porang (Amorphophallus muelleri) seedlings. This study used a non-factorial randomized block design (RAK). The treatment factor was the composition of the growing media which consisted of 7 levels of treatment, namely: A = Topsoil ultisol 100%, B = 100% goat manure, C = 100% sand, D = Topsoil ultisol + goat manure + sand (1 : 1: 1 : 1), E = Topsoil ultisol + goat manure + sand (1 : 2: 1), F = Topsoil ultisol + goat manure + sand (2 : 1: 1), G = Topsoil ultisol + goat manure + sand ( 1:1:2). The parameters observed were the percentage of germination, plant height, stem diameter and leaf area of the plant. Based on the results of the study, it can be stated that the composition of a mixture of topsoil ultisol, goat manure and sand has a significant effect on the growth of porang seedlings. The best growth of porang seedlings was found in the composition of topsoil, sand and goat manure with a ratio of 1: 1: 2 (E). The application of goat manure and sand on top soil ultisol had a significant effect on plant height, stem diameter and leaf area, but had no significant effect on the percentage of seedling growth.